2015
DOI: 10.1093/eurpub/ckv043
|View full text |Cite
|
Sign up to set email alerts
|

Health literacy in Europe: comparative results of the European health literacy survey (HLS-EU)

Abstract: Background: Health literacy concerns the capacities of people to meet the complex demands of health in modern society. In spite of the growing attention for the concept among European health policymakers, researchers and practitioners, information about the status of health literacy in Europe remains scarce. This article presents selected findings from the first European comparative survey on health literacy in populations. Methods: The European health literacy survey (HLS-EU) was conducted in eight countries:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

139
1,470
51
152

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,694 publications
(1,951 citation statements)
references
References 8 publications
139
1,470
51
152
Order By: Relevance
“…The level of health literacy tells us how an individual understands the instructions that he or she receives within the healthcare system, how he or she functions within the healthcare system, and that is why with its help it is possible to predict, how healthy an individual is going to be in future [26]. That is extremely important when taking into consideration more vulnerable population groups, such as older adults, the group which can nowadays be linked to multimorbidity, loneliness and related health and social problems.…”
Section: Discussionmentioning
confidence: 99%
“…The level of health literacy tells us how an individual understands the instructions that he or she receives within the healthcare system, how he or she functions within the healthcare system, and that is why with its help it is possible to predict, how healthy an individual is going to be in future [26]. That is extremely important when taking into consideration more vulnerable population groups, such as older adults, the group which can nowadays be linked to multimorbidity, loneliness and related health and social problems.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time however, some participants reported poor knowledge of their medications, a common trait among patients taking multiple drugs, and older people in general tend to have poorer health literacy. (28,33,34) This highlights the complex interplay of strong beliefs in the context of limited knowledge. Indeed, a previous study involving frail older patients found no relationship between strong beliefs and medication knowledge.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…Bisherige Studien weisen darauf hin, dass eine eingeschränkte GK negative Auswirkungen auf den Gesundheitszustand, das Gesundheitsverhalten, bestimmte Risikofaktoren und die Nutzung und Kosten der Gesundheitsversorgung hat [2,10,[12][13][14]. Dabei ist zu berücksichtigen, dass die Ausprägung der GK in der Bevölkerung nicht gleich verteilt ist.…”
Section: "Gesundheitskompetenz Ist Mit Der Leseund Schreibfähigkeit Vunclassified
“…Dabei ist zu berücksichtigen, dass die Ausprägung der GK in der Bevölkerung nicht gleich verteilt ist. Bevölkerungs-gruppen mit besonders geringer GK sind häufig durch einen niedrigen Bildungsstand, geringes Einkommen, einen Migrationshintergrund, einen schlechten Gesundheitszustand und ein hohes Lebensalter gekennzeichnet [2,10,[14][15][16]. Daher werden zunehmend Interventionen zur Verbesserung der GK entwickelt, besonders für Patientinnen und Patienten in der Gesundheitsversorgung [17,18], aber auch für Bevölkerungsgruppen mit spezifischen Risiken oder Erkrankungen [13,[19][20][21].…”
Section: "Gesundheitskompetenz Ist Mit Der Leseund Schreibfähigkeit Vunclassified